PENGARUH PENERAPAN NHT TERHADAP HASIL BELAJAR IPS SISWA KELAS V SDN 03 PONTIANAK KOTA - Langit, Sylvester; Marli, Suhardi; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of NHT application on learning outcomes of social studies students of fifth grade elementary school 03 Pontianak Kota. The research method used was an experiment with the form of Quasi Experiment Design and the research design for Nonequevalent Control Group Design. The population is all class V, amounting to 96 people, research samples of students in class V B which amounted to 34 students as the experimental class and students of class V C which amounted to 34 students as the control class. Data collection techniques using measurement techniques and data collection tools are written tests of objective forms in the form of multiple choices. The results obtained by the average control class final test 74.88 and the average test end of the experimental class 79.18. The results of the final test t-test obtained tcount of 2.21 and t table (? = 5% with dk = 66) of 1.66, which means thitung (2.21)> t table (1.66), then Ha is accepted. So, it can be concluded that there is the effect of implementing NHT on the learning outcomes of fifth grade students of SDN 03 Pontianak Kota. Calculation of Effect Size (ES), obtained ES for 0.52 (medium category). Based on these calculations, it can be said that the application of NHT has a positive influence on social studies learning outcomes of students in Class V SDN 03 Pontianak Kota.Keywords: NHT, Social Sciences, Learning Outcome